Penerapan Teknik Backward Chaining untuk Meningkatkan Kemampuan Dental Hygiene pada Anak Tunagrahita di SDLB Bhakti Luhur Maumere : Studi Kasus - Fransiska Mitang Sika, Odelbertha; Nona Fembi, Pembronia (Pustaka Galeri Mandiri, 2026)
Children with intellectual disabilities have limitations in self-care, attention, memory, communication, and fine motor coordination. These conditions may affect their ability to maintain dental hygiene, particularly toothbrushing, which is an essential daily self-care activity. This case study aimed to describe the application of the backward chaining technique to improve dental hygiene independence among children with intellectual disabilities. The study involved two children at SDLB Bhakti Luhur Maumere who had difficulty brushing their teeth independently. Data were collected through direct observation, nursing assessment forms, toothbrushing skill checklists, and daily SOAP progress notes. The intervention was implemented for six consecutive days by training the children from the final step of toothbrushing to the initial steps, supported by simple instructions, demonstration, gradual assistance, and positive reinforcement. The results showed improved toothbrushing skills in both children, although the level of progress differed according to their motor ability, concentration, and understanding of instructions. The children became more able to hold the toothbrush, follow simple instructions, perform several toothbrushing steps, and reduce dependence on assistance. The findings indicate that backward chaining can be used as a structured nursing intervention to improve dental hygiene independence in children with intellectual disabilities.